My war criminal: personal encounters with an architect of genocide - Stern, Jessica (Ecco, an imprint of HarperCollins Publishers, 2020)
The mesmerist -- Visiting the poet in prison -- Hatred and fear -- Victims -- Petnjica -- Visiting the poet's family -- The poet becomes a politician -- Martyrs -- The hunt -- Houdini -- Moral hazard -- Fear -- The return of nationalism -- The problem of evil.